Ebola outbreak in Nigeria: perceptions from commercial motorcyclists and passengers in Ibadan, Nigeria. Issue 1 (24th December 2018) - Salami, Kabiru K; Ayegboyin, Matthew; Adedeji, Isaac A
Abstract: The outbreak of deadliest and most widespread Ebola virus disease (EVD) in West African countries was not only unexpected but also sudden in places like Nigeria. The epidemic was an indication of weak health systems characterised by inadequate precautions and low knowledge of containment. Although Nigeria was able to contain EVD much earlier, people's perception, which also influenced their responses, might enhance the spread and retard containment. This study utilized 25 in-depth interviews conducted with commercial motorcycle–taxi (Okada) riders in key locations in Ibadan, Oyo state, to document their perception about EVD outbreak. Series of sociocultural practices such as handshaking, hugging and embracement identified were favourable to transmission of EVD and affected containment. Regular handwashing was difficult and not cost-effective to practice. The perceived trust in God's intervention could make treatment seeking and prevention slower to achieve. The potential of sociocultural practices, such as handshaking and hugging, as driver for transmission of EVD may influence the perception of motorcycle–taxi riders in the prevention and containment activities in Nigeria. Hence, understanding people's perception on handwashing practices, hugging and butchering of bushmeat should be given priority in designing programmes of EVD prevention and control in Nigeria.